2001
DOI: 10.1152/ajpcell.2001.281.2.c532
|View full text |Cite
|
Sign up to set email alerts
|

Identification of mediators stimulating proliferation and matrix synthesis of rat pancreatic stellate cells

Abstract: The aim of this study was to identify fibrogenic mediators stimulating activation, proliferation, and/or matrix synthesis of rat pancreatic stellate cells (PSC). PSC were isolated from the pancreas of normal Wistar rats and from rats with cerulein pancreatitis. Cell activation was demonstrated by immunofluorescence microscopy of smooth muscle alpha-actin (SMA) and real-time quantitative RT-PCR of SMA, fibronectin, and transforming growth factor (TGF)-beta(1). Proliferation was measured by bromodeoxyuridine inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
165
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(170 citation statements)
references
References 44 publications
5
165
0
Order By: Relevance
“…[51][52][53] As a result of increased recruitment of inflammatory cells, activated mononuclear cells release profibrotic cytokines and chemokines, such as TGF-b, TNF-a and MCP-1, which in turn activate hPSCs and promote fibrosis in CP. 4,52,53 The chemokine MCP-1, one of the major monocyte chemoattractants, is highly expressed in fibroblasts in CP, induces TGF-b upregulation and is associated with the progression of pancreatic fibrosis. 52,54 Blocking of MCP-1 attenuates the degree of fibrosis in experimental CP.…”
Section: Discussionmentioning
confidence: 99%
“…[51][52][53] As a result of increased recruitment of inflammatory cells, activated mononuclear cells release profibrotic cytokines and chemokines, such as TGF-b, TNF-a and MCP-1, which in turn activate hPSCs and promote fibrosis in CP. 4,52,53 The chemokine MCP-1, one of the major monocyte chemoattractants, is highly expressed in fibroblasts in CP, induces TGF-b upregulation and is associated with the progression of pancreatic fibrosis. 52,54 Blocking of MCP-1 attenuates the degree of fibrosis in experimental CP.…”
Section: Discussionmentioning
confidence: 99%
“…15,17 After TGFb1 treatment, RNA isolation and RT-PCR or Western blot analysis was performed as described above.…”
Section: Response To Tgfb1 Stimulationmentioning
confidence: 99%
“…These include cytokines (eg IL-1), growth factors (PDGF, TGFb1), ethanol and acetaldehyde. 11,15,16 Platelet-derived growth factor (PDGF) seems to be the most potent mitogen, whereas transforming growth factor b 1 (TGFb1) predominantly induces matrix synthesis. 15,17 Different methods for isolation of these cells have been published, using either dispersed acini, enzymatic tissue digestion and density centrifugation, or outgrowth of PSC from pancreatic tissue.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…PSCs are considered the major ECM producing cells in pancreas 49,50 . Previous studies have shown that PSCs are transiently activated in experimental models of pancreatitis in rodents and contribute to organ repair.…”
Section: Pancreatic Stellate Cells Were Persistently Activated In Plgmentioning
confidence: 99%